Mystery and Meaning - B Kuppuswamy (Journal of Dharma, 2020)
The book bears the subtitle: "Personal Logic and the Langu- age of Religion." The book consists of an introductory chapter and three parts. The first part is entitled "The Context of Theology"; the second part deals with "The Language of Theology"; and the third part is "Toward a Dialogical Theology".